Eksitensi Mahasiswa PPL Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Muhammad Husaini (https://journal.metanusantara.com/pedagogia, 2024)
This study aims to analyse the role of Field Experience Practices (PPL) students in increasing student learning motivation in Islamic Religious Education (PAI) subjects. Using a qualitative approach with a case study method, the main data sources of this research include PPL students, students, and supervising teachers in the schools where PPL is conducted. Data were collected through in-depth interviews, participatory observation, and analysis of related documents. The results showed that the presence of PPL students significantly contributed to increasing students' learning motivation. PPL students implemented various innovative teaching strategies, such as the use of interactive learning media and a personalised approach in guiding students. Students reported increased enthusiasm and understanding of PAI materials during the PPL period. In addition, the supervising teacher observed an increase in students' active participation in the learning process.